Comparative study and genetic diversity of Salicornia persica (Chenopodiaceae) using SCOT molecular markers - Liu, Ziyu; Esfandani-Bozchaloyi, Somayeh (Phytotaxa, 2022)
Salicornia is a cosmopolitan genus having a high complicate taxonomy even described as a nightmare. Morphologically members of Salicornia are halophyte, annual, articulated, and succulent herbs with cortical palisade, opposite decussate scale-leaves, thyrsoid cymes, flowers packed in cauline depressions and the diaspore composed of l-seeded utricle. Salicornia is a priceless edible vegetable, considered as a favourable resource for cultivation in arid and semiarid coastal zones. Concerning the molecular data, although various studies were published, the situation is still quite obscure, at least for some taxa. Also, no DNA markers were used to analyses the genomic variability of the populations, up to date. In the present study, the genetic diversity of 102 individuals of S. persica (15 populations) were studied using 10 Start Codon Targeted (SCoT) markers. High polymorphic bands (94.18%), polymorphic information content (0.27), and allele number (1.38) showed SCoT as a reliable marker system for genetic analysis of this species. We used SCoT molecular marker for our genetic investigation with the following aims: 1) investigate genetic diversity both among and with date S. persica, 2) identify genetic groups within the 15 populations studied, and 3) produce data on the genetic structure of S. persica populations. The results obtained revealed a high within-population genetic variability.